Si-Ge whiskers for thermoelectric sensors design - Druzhinin, A.A.; Ostrovskii, I.P.; Khoverko, Yu.M.; Liakh-Kaguy, N.S. (Physics and Chemistry of Solid State, 2020)
The paper deals with studies of thermoelectric properties for Si1-xGex (x=0.01-0.05) whiskers doped with boron during their growth by CVD method. Temperature dependences of the resistance and the Seebeck coefficient for Si1-xGex whiskers were measured in the temperature range 275–550 K. A method for determination of thermoelectric parameters of the whisker was proposed with use of the whisker joints, which allows us to define a ratio of Seebeck coefficient to thermal conductivity a/k. Taking into account the obtained values of Seebeck coefficient, the whisker conductance and estimated values of thermal conductivity, parameter ZT was calculated for the whiskers and consists of 0.15 for T=200oC. The obtained value of ZT is in good coincidence with literature data for hop pressed Si-Ge nanocomposites. The humidity sensor was designed base on Si-Ge whiskers.